Assessment of Poly Pharmacy and Inappropriate Prescriptions in Geriatrics in SCCL Main Hospital - BOLLA NITHIN; MOREM NAGARAJU (International Journal of Pharma and Bio Sciences, 2018)
The proportion of elderly population has been constantly increasing over last few years in India and are potentially at greater risk of medication errors. Beers criteria and other guidelines have been developed to assist in the reduction of potentially inappropriate medications prescribed to elderly patients. The aim of this study is to evaluate the inappropriate prescription to elderly population. This was a prospective observational study of elderly patients(ï‚³60years) in the inpatient department in a tertiary care hospital. The data was collected in a pre-structured data collection form. American Geriatrics Society Beers criteria (2015) was used to screen potentially inappropriate medications. 178 patients were studied on an average of 7.01 ï‚± 1.8 drugs per prescription. Inappropriate medication prescriptions(IMP) were found in about 48%. Categories with highest IMP includes Benzodiazepines 36.52% followed by Gastro intestinal 26.07%, drugs acting on cardiovascular system 17.39%, NSAIDs 13.04%, Antispasmodics 5.21% and Anticholinergics 1.73%. Approximately every second prescription is inappropriate. Inappropriate prescribing is influenced by the total number of drugs prescribed to elderly patients, which shows a trend towards polypharmacy (>5 drugs) which has to be viewed with caution e.g. by computerized clinical decision support, pharmacist etc.…Focused and systematic interventions are needed to improve the quality of medication prescription in this patient group.